Investigating Factors Associated to Speech and Language Development Problem Among Under-five Children in Bangladesh: A Cross-Sectional Study - Farhana Afrin Duty (International Journal of Children, 2025)
Speech and Language Delay (SLD) is a developmental disorder characterized by a lag in a child's acquisition and use of spoken language compared to typical developmental milestones. It is a significant developmental concern with profound implications for cognitive, social, and academic outcomes. The objective of this study is to explore the factors associated to SLD in children and early intervention of the problem to support the children who need special care. This study investigates the factors associated with speech and language delay (SLD) in children in Bangladesh, a context where comprehensive national data on this issue is scarce. The research utilizes a sample of 128 children, assessing several variables and found the significant factors such as gender, breastfeeding duration, neurodevelopmental issues, and the achievement of age-specific milestones. Significant factors associated with Speech and Language Delay are identified with the help of various statistical methods, such as chi-square tests, t-tests, and logistic regression analyses. Key findings reveal that males, shorter breastfeeding durations, presence of neurodevelopmental issues, higher income family, smaller family structure, and lower achievement of developmental milestones significantly increase the risk of SLD. The research emphasizes on the need for timely support and specialized assistance in reducing the risk of SLD in children, offering essential guidance for healthcare providers and caregivers. For this purpose, the checklists are recommended for developmental milestones for communication developed by American Speech-Language-Hearing Association in 2023 which is found to be highly associated with the observed speech delay problem among children. This research contributes to the understanding of SLD in the Bangladeshi context, laying a foundation for tailored interventions to promote optimal communication development.
Keywords: Age-specific milestones; Speech and Language Delay (SLD); cognitive development; communication development; developmental Disorder; specialized assistance